Shorter halving time of BCR‐ABL1 transcripts is a novel predictor for achievement of molecular responses in newly diagnosed chronic‐phase chronic myeloid leukemia treated with dasatinib: Results of the D‐first study of Kanto CML study group. Issue 4 (2nd March 2015) - Iriyama, Noriyoshi; Fujisawa, Shin; Yoshida, Chikashi; Wakita, Hisashi; Chiba, Shigeru; Okamoto, Shinichiro; Kawakami, Kimihiro; Takezako, Naoki; Kumagai, Takashi; Inokuchi, Koiti; Ohyashiki, Kazuma; Taguchi, Jun; et al.
Abstract : To investigate the factors that affect molecular responses on dasatinib treatment in patients with chronic‐phase chronic myeloid leukemia (CML‐CP), we performed a clinical trial named the "D‐First study." Fifty‐two patients with newly diagnosed CML‐CP were enrolled in this study and received 100 mg dasatinib once daily. A deep molecular response (DMR) was defined as <50 copies/μg RNA of BCR‐ABL1 transcript value corrected by GAPDH, which ensures <0.01% of BCR‐ABL1 transcript value according to International Scale ( BCR‐ABL1 IS ). The halving time for BCR‐ABL1 transcripts was calculated using transcript levels before dasatinib treatment, transcript levels after 3 months of treatment, and the treatment time between these two points. In terms of molecular response, 38 of 51 (75%) patients reached major molecular response (MMR) by 12 months, and the rate of DMR by 18 months was 59% (30/51). While both BCR‐ABL1 transcript levels before treatment and a shorter halving time of BCR‐ABL1 transcripts (≤14 days) were significant factors affecting achievement of MMR by 12 months, the Sokal score at diagnosis was not associated with MMR. Importantly, the halving time was the only factor that predicted achievement of DMR by 18 months. We showed that patients with CML‐CP treated with dasatinib can be stratified according to the early treatment response as determined by the halving time of BCR‐ABL1 transcripts. These data emphasize the significance of the early response from dasatinib treatment in achieving a DMR. (ClinicalTrials.gov ; NCT01464411) Am. J. Hematol. 90:282–287, 2015. © 2014 Wiley Periodicals, Inc.